Response to Michael Sells - Green, Ronald Michael (Journal of religious ethics, 2015)
In an era when lies and misrepresentations about historical events easily become firmly rooted, Michael Sells's discussion illustrates the importance of careful historical research as a moral enterprise. In addition to the skills of the historian, however, there is also room in this enterprise for those of the ethicist. In particular, I warn against confusing the truth or falsity of claims about one narrow historical period with larger questions about the moral meaning and significance of those claims. Illustrating this, I argue one cannot assess the legitimacy of competing nationhood claims solely on the basis of the deeds of specific actors. Nor should the actions of a single individual like the Grand Mufti of Jerusalem be converted into a totalizing claim about the rights of the Palestinian people.